Antibiotic Sensitivity Pattern Among Diabetic Outpatients with Urinary Tract infection in Pontianak - Mardhia Mardhia; Mahyarudin Mahyarudin; Abror Irsan (Indonesian Society for microbiology, 2020)
Diabetic patients are associated with a higher risk of infection. The research purposed to identify antibiotic susceptibility patterns among diabetic outpatients with urinary tract infection in Pontianak. An experimental study was performed for 13 bacterial isolates of diabetic outpatients with urinary tract infection in the Clinic of Diabetes Mellitus, Sultan Syarif Mohamad Alkadrie Hospital, Pontianak. The disc diffusion method was used to perform the susceptibility of antibiotics to the bacterial isolates. Among 13 isolates, the most common causative agent of urinary tract infection was Escherichia coli (53.85%), followed by Pseudomonas aeruginosa (30.77%). Klebsiella spp and Enterobacter aerogenes were 7.69%. Most isolates of bacteria of the study had a high sensitivity to Cefepime (92.31%), then followed by Levofloxacin, Amikacin, and Meropenem for 84.62%. The study revealed low sensitivity of bacteria to Amoxicillin/Clavulanate, Co-Trimoxazole, Cefazoline and Ceftriaxone (30.77%, 23.08 %, 23.08%, 23.08%, respectively). All bacterial isolates had high resistance to Ampicillin. Moreover, multidrug resistance observed among bacterial isolates. Keywords: antibiotic susceptibility, diabetes, urinary tract infections